223k views
4 votes
Solve the equation. X^5-5x^3+4x=0

2 Answers

4 votes

Answer:

0, +/- 1. +/- 2

Explanation:


x^(5) -5x^(3) +4x=0 Write the equation in the form of P(x) = 0.


x(x^(4) - 5x^(2) + 4) = 0 Factor out the GCF, x.


x(x^(2))^(2) - 5x^(2) + 4 = 0 Factor
(x^(2))^(2)- 5x^(2) + 4 = 0.


x = 0,
(x^(2))^(2) - 5x^(2) + 4 = 0 Let a =
x^(2) and substitute.


a^(2) - 5a + 4 = 0 Factor.


(a - 4)(a - 1) = 0 Replace a with
x^(2).


(x^(2) - 4)(x^(2) -1) = 0 Factor
(x^(2) - 4) as a difference of squares.


(x -2)(x+2)(x^(2) -1) = 0 Use the Zero Product Property


x = 2, x = -2, x^(2) = -1


x = 0, 1, -1, 2, -2

Solve the equation. X^5-5x^3+4x=0-example-1
User Draw
by
5.9k points
2 votes

Answer:

Wait

Explanation:

Is a equation or polynomial

User Bilesh Ganguly
by
5.0k points